To convert the recursive form given by \( a_1 = 5 \) and \( a_n = 2a_{n-1} \) to an explicit form, we can first observe the pattern in the terms:
- \( a_1 = 5 \)
- \( a_2 = 2a_1 = 2 \times 5 = 10 \)
- \( a_3 = 2a_2 = 2 \times 10 = 20 \)
- \( a_4 = 2a_3 = 2 \times 20 = 40 \)
From these calculations, we can see that:
- \( a_1 = 5 \)
- \( a_2 = 5 \times 2^1 = 10 \)
- \( a_3 = 5 \times 2^2 = 20 \)
- \( a_4 = 5 \times 2^3 = 40 \)
Following this pattern, we can deduce the explicit formula:
\[ a_n = 5 \times 2^{n-1} \]
Now we can match this with the given options:
- (4) \( a_n = 5(2)^{n-1} \)
- This matches with our derived explicit form.
Thus, the correct response is:
\( a_n = 5(2)^{n-1} \)
A sub n is equal to 5 times 2 raised to the n minus 1 power.